Distribution and sources of organic matter in surface marine sediments across the North American Arctic margin. Issue 9 (5th September 2013) - Goñi, Miguel A.; O'Connor, Alison E.; Kuzyk, Zou Zou; Yunker, Mark B.; Gobeil, Charles; Macdonald, Robie W.
<x xml:space="preserve">Abstract</x> [1] As part of the International Polar Year research program, we conducted a survey of surface marine sediments from box cores along a section extending from the Bering Sea to Davis Strait via the Canadian Archipelago. We used bulk elemental and isotopic compositions, together with biomarkers and principal components analysis, to elucidate the distribution of marine and terrestrial organic matter in different regions of the North American Arctic margin. Marked regional contrasts were observed in organic carbon loadings, with the highest values (≥1 mg C m−2 sediment) found in sites along Barrow Canyon and the Chukchi and Bering shelves, all of which were characterized by sediments with low oxygen exposure, as inferred from thin layers (<2 cm) of Mn oxihydroxides. We found strong regional differences in inorganic carbon concentrations, with sites from the Canadian Archipelago and Lancaster Sound displaying elevated values (2–7 wt %) and highly depleted 14C compositions consistent with inputs from bedrock carbonates. Organic carbon:nitrogen ratios, stable carbon isotopes, and terrigenous organic biomarkers (lignin phenols and cutin acids) all indicate marked regional differences in the proportions of marine and terrigenous organic matter present in surface sediments. Regions such as Barrow Canyon and the Mackenzie River shelf were characterized by the highest contributions of land‐derived organic matter, with compositional characteristics that suggested distinct sources and provenance. In contrast, sediments from the Canadian Archipelago and Davis Strait had the smallest contributions of terrigenous organic matter and the lowest organic carbon loadings indicative of a high degree of post‐depositional oxidation.